Unionization structures in international oligopoly - Beatrice Pagel; Christian Wey (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2012)
We examine how competition in international markets affects a union's choice of wage regime which can be either uniform or discriminatory. Firms are heterogenous with regard to international competition. When unions choose their wage regimes sequentially, a discriminatory outcome becomes more likely when international competition increases. However, for intermediate levels a union may stick with a uniform wage regime even if the rival union adopts a discriminatory regime. When competition is sufficiently intense, both unions revert to the discriminatory regime. Paradoxically only in those latter instances all parties (consumers, workers and firms) may be better off (each in aggregate) if all unions adopt a uniform wage regime. We conclude that union incentives to coordinate their wage regimes should then also become largest.
Keywords: D43; J51; L13; 330; Unionization; International Oligopoly; Uniform Wages; Tarifpolitik; Lohnpolitik; Internationaler Wettbewerb; Oligopol; Theorie